Morpho-anatomical and Physiological Traits related to Abiotic and Biotic Stress Resistance of Cotton: Hypothesis - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
Cotton plays an important role in our society and is called as white gold for its high economic importance. Significant research advances have been attained for its genetic improvement of cotton for yield, fibre quality and drought resistance. Incorporation of Bt cotton has contributed a lot to its productivity for insect resistance, but the level of resistance is going down probably due to the development of immunity of the insects. The abiotic stresses can broadly be categorized as edephic, atmospheric and geographic stresses. The soil, besides being intergral part of rhizosphere, is the prime source of water and most of the nutrient elements to the plant. The main edephic factors that cause stress to plant are water, salt, soil temperature, nutrition, physical and chemical composition etc. Among the atmospheric factors, cardinal temperature, solar radiation, relative humidity…..